Effect of Environmental Parameters on Soil Salinity on Plant - M. Almudhafar, Safaa; B.A. , Almayahi (International Journal of Psychosocial Rehabilitation, 2020)
This study consisted of the determination of the trace metals and physiochemical properties in plant samples (eggplant, chard plant, palm fronds, alfalfa, tarfa, and mung plant) in the summer season and (chard, dill, wheat, palm fronds, alfalfa, and spinach) in the winter season from the al-Heera region in Najaf City of the Republic of Iraq, where plant samples are not treated before they are consumed. The purpose was to ascertain the quality of plants from these sources. It was taken from ten sampling points and analyzed for the following (EC, TDS, Na, Ca, Mg, K, Cl, and SO₄) using the procedure outlined in the photometer method (flame absorption spectrometer) used for analyzing the samples. The contamination by heavy metals in plants is one of the major issues to be faced throughout the world and requires attention because heavy metals above their normal ranges are extremely threatening to both plant and animal life. It was therefore of interest to conduct a study to estimate levels of heavy metals in plants. Plant samples were analyzed separately for their roots, stems, and leaves. The data showed the variation of the investigated parameters in plants. The concentrations of most of the investigated parameters in the plant samples from the Al-Heera region were above the permissible limits of the World Health Organization.